2017
DOI: 10.14810/ijmech.2017.6101
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Bending Analysis of a Circular Sandwich Plate Under Distributed Load

Abstract: In this paper, bending analysis of a circular sandwich plate under distributed load with simply supported and clamped boundary conditions is investigated. First, the governing equations of the circular sandwich plate are obtained and they are solved using the Bessel functions. Then in order to validate the correctness of analytical results, numerical finite element method is used and its results are presented in the forms of contours and graphs. The results indicate that under distributed load, maximum deflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The investigation focuses on the bending analysis of a circular sandwich plate subjected to a distributed load under both simply supported and clamped boundary conditions. A comparison between analytical and numerical methods reveals that the analytical approach yields acceptable accuracy in the results [7]. Numerous tensile tests were conducted on architectural cores to analyze and comprehend the impact of topology and core density on the Poisson's ratio and Young's modulus of these architectural structures [8].…”
Section: Introductionmentioning
confidence: 99%
“…The investigation focuses on the bending analysis of a circular sandwich plate subjected to a distributed load under both simply supported and clamped boundary conditions. A comparison between analytical and numerical methods reveals that the analytical approach yields acceptable accuracy in the results [7]. Numerous tensile tests were conducted on architectural cores to analyze and comprehend the impact of topology and core density on the Poisson's ratio and Young's modulus of these architectural structures [8].…”
Section: Introductionmentioning
confidence: 99%
“…The face-sheet can be made of metal or composite materials and the core can be made of reinforced and unreinforced foamed plastics, rubber, balsa, metal in the form of corrugated sheet, cellular elements, etc. (Zadeh & Masoud, 2017) investigated the bending analysis of a circular sandwich plate under distributed loads with both simply supported and clamped boundary conditions, the governing equations of the circular sandwich plate are obtained and solved using the Bessel functions, validated using the finite element method. The results indicated that under distributed load, maximum deflection happens at 0.3 of outside radius, away from the centre, and minimum deflection occurs at the outer edge of the circular sandwich plate.…”
Section: Introductionmentioning
confidence: 99%